COMMUNICATION STRATEGY IN STUDENTS ’ ROLEPLAY AS FOUND IN BUSINESS ENGLISH MARKETING COMMUNICATION ( A CASE STUDY IN ENGLISH DEPARTMENT FHB UNISBANK SEMARANG) - Endang Yuliani Rahayu; Katharina Rustipa; Yulistiyanti, Yulistiyanti; Teguh Kasprabowo (Media Bina Ilmiah, 2025)
Speaking in English  for students of English department  is challenging activity. They like this  subject as  they can convey their idea in the target language to the listeners. During their process of communication in role play in the Business English Marketing Communication classroom  they may find difficulties due to their lack of knowledge in the target language. Referring to  Dornyei who defines communication strategy as  a systematic technique  used by the speakers  to express  their meaning  when they  face some difficulties.  By  applying descriptive qualitative method,  the reseachers  refered  to Dornyei’s theory of Communication Startegy to analyze the 215 data. The most frequently  communication strategy used were  approximation,  avoidance and Hesitation /gambit. Meanwhile negosiation, code switching, literal translation, hesitation/gambits and time gaining /filler  have been used  for 3 times by the students. The purpose of applying communication strategy were mostly for overcoming their difficulties, to express certain  intention, to master language competence  and maintain the communication with his partner